2008
DOI: 10.1901/jaba.2008.41-291
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Vocal Stereotypy and Therapist Fading

Abstract: A functional analysis for a boy with Down syndrome and autism suggested that vocal stereotypy was maintained by automatic reinforcement. The analysis also showed that instructions and noncontingent attention suppressed vocal stereotypy. A treatment package consisting of noncontingent attention, contingent demands, and response cost effectively reduced vocal stereotypy. The treatment package remained effective even when noncontingent attention was removed, making the procedure easier to implement. Also, the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
60
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 13 publications
2
60
0
Order By: Relevance
“…Thus, a no interaction condition was conducted in place of the alone condition for all but one participant. For Sally, a no consequence condition was conducted in place of a no interaction condition (Athens, Vollmer, & Sloman, 2008). This condition was conducted as it was observed that in the absence of tangibles, Sally engaged in thumb sucking, which was incompatible with vocal stereotypy.…”
Section: Functional Analysismentioning
confidence: 99%
“…Thus, a no interaction condition was conducted in place of the alone condition for all but one participant. For Sally, a no consequence condition was conducted in place of a no interaction condition (Athens, Vollmer, & Sloman, 2008). This condition was conducted as it was observed that in the absence of tangibles, Sally engaged in thumb sucking, which was incompatible with vocal stereotypy.…”
Section: Functional Analysismentioning
confidence: 99%
“…Again, behavioral intervention research can be subdivided into two overarching categories—consequence-based and antecedent-based interventions. Some of the consequence-based intervention strategies that have been used to treat stereotypies (e.g., repetitive vocalizations) and/or SIB in ASD and other developmental disabilities, include physically or verbally (e.g., saying, “no”) blocking the individual from engaging in the behavior (i.e., response interruption and redirection/response blocking) (Ahearn et al 2007; Koegel et al 1974; Liu-Gitz and Banda 2010), removal of a positive consequence when the stereotypic behavior occurs (i.e., response cost procedures) (Athens et al 2008; Sidener et al 2005), reinforcing other behaviors the individual displays instead of the problematic behavior (i.e., differential reinforcement) (Azrin et al 1988) and functional communication training (FCT; Kennedy et al 2000). FCT is a multi-component intervention that involves teaching the individual an appropriate communication response that can be used to obtain the same reinforcer as the inappropriate behavior, while simultaneously withdrawing reinforcement of the inappropriate behavior (i.e., extinction) (Carr and Durand 1985).…”
Section: A Framework For Behavioral and Psychosocial Interventions Fomentioning
confidence: 99%
“…Both vocal RIRD and motor RIRD were effective in reducing the level of vocal stereotypy for all four subjects without the requirement of compliance with instructions. RIRD has also been evaluated as a component of larger treatment packages in several studies (Athens, Vollmer, Sloman, & St. Peter Pipkin, 2008;Col on, Ahearn, Clark, & Masalsky, 2012;Dickman, Bright, Montgomery, & Miguel, 2012;Love, Miguel, Fernand, & LaBrie, 2012;Miguel, Clark, Tereshko, & Ahearn, 2009).…”
mentioning
confidence: 99%